Effect of ghee residue on growth performance and economics of production of native chicken - RAMESH, P; VALAVAN, S EZHIL; GNANARAJ, P TENSINGH; OMPRAKASH, A V (The Indian Journal of Animal Sciences, 2018)
The biological experiment was designed to study the effect of feeding ghee residue in native chicken (Aseel) for a period of 12 weeks on various parameters, viz. bi-weekly body weight, gain in body weight, feed consumption, feed conversion ratio, livability and the cost effectiveness of feeding ghee residue. A total of 300 day-old, unsexed, Aseel native chicken belonging to single hatch were utilized for this study. The treatment groups were fed with diets containing ghee residue at different inclusion levels, i.e. 0% (T1-control), 5% (T2), 10% (T3) and 15% (T4). Biological experiment revealed that there was significant difference in body weight and body weight gain and feed conversion ratio and no significant difference was observed in feed consumption and livability. The cost effectiveness of the native chicken fed with various levels of ghee residue showed increased net profit per kg live weight in the group fed 5% ghee residue.